University of the East’s Commitment to Corporate Social Responsibility: A Comprehensive Overview of Initiatives and Programs (A Review of Related Literature) - Ramos, Shyla; Atienza, Atienza; Hudtohan, Emiliano T. (International Journal of Management and Education in Human Development, 2024)
s